Low baseline (pre-injury) blood pressure predicts inpatient mortality in elderly trauma patients: A bi-institutional study. Issue 6 (December 2016) - Bohnen, Jordan D.; Chang, David C.; Ramly, Elie P.; Olufajo, Olubode A.; Le, Ryan T.; Kaafarani, Haytham M.A.; Yeh, Daniel Dante; King, David R.; Fagenholz, Peter J.; Butler, Kathryn L.; Askari, Reza; Salim, Ali; et al.
Abstract : OBJECTIVE: The relationship between baseline (i.e., pre-injury) blood pressure and trauma outcomes in elderly patients is unknown. We therefore aimed to identify the independent impact of baseline systolic blood pressure (SBP) on inpatient mortality among elderly trauma patients. METHODS: The 2004 to 2014 trauma registries of two Level I Trauma Centers were linked to electronic health records then reviewed to identify patients ≥65 years old with available baseline vital signs. Baseline SBP was defined as mean outpatient SBP within 2 years before injury. Trauma SBP was defined as first SBP reading after presentation for trauma. Baseline and Trauma SBP were classified as Low (<110 mm Hg), Normal (110–139 mm Hg), or High (≥140 mm Hg). Logistic multivariable regression models were constructed to assess the independent impact of Baseline SBP on inpatient mortality, controlling for demographics, comorbidities, injury mechanism/severity, and Trauma SBP. RESULTS: Of 37, 494 patient admissions, 4, 233 met inclusion criteria. Median age was 81 years; 63.6% were female. Mortality was 5.39%. In unadjusted analyses, mortality rates were 11.01%, 5.28%, and 4.52% in the Low, Normal, and High Baseline SBP groups, respectively ( p = 0.001). In multivariable analyses, patients with Low Baseline SBP had significantly increased mortality risk [OR 3.19 (95% CI 1.62–6.26), p = 0.001] compared to patients with Normal Baseline SBP, in particular when they presented with Low Trauma SBP (<110 mm Hg) [OR 6.14 (2.17–17.36), p = 0.001] or Normal Trauma SBP (110–139 mm Hg) [OR 3.87 (1.43–10.45), p = 0.008]. The mortality risk associated with Low Baseline SBP was particularly elevated among patients with a pre-existing diagnosis of hypertension [OR 4.78 (1.97–11.62), p = 0.001]. CONCLUSION: Low baseline pre-injury SBP is independently associated with more than a threefold increase in inpatient mortality among elderly trauma patients and a fivefold increase in mortality risk among patients with pre-existing hypertension. Given that blood pressure control in the elderly offers a long-term survival advantage, the paradoxical finding of decreased survival after trauma warrants further investigation. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.